Direct electric curing anti-radiation ultra-high performance concrete and preparation method thereof

By using iron radiation-proof aggregates, conductive fibers and metal conductive powders in radiation-proof ultra-high performance concrete, the ratio and conductive network design are optimized, and the problems of low heating efficiency of direct electrocuring methods and difficult to form conductive networks are solved. , achieving efficient and stable high-temperature maintenance and ray shielding effects.

CN119263728APending Publication Date: 2025-01-07ANHUI UNIVERSITY OF ARCHITECTURE
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411339379.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-25
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

The existing direct electrocuring methods have limited heating efficiency for radiation-proof ultra-high performance concrete, especially in cold environments, and conductive fillers increase material cost and reduce strength, and conductive networks are difficult to form.

Method used

Using iron radiation-proof aggregates, conductive fibers and metal conductive powders, the conductive properties of concrete are improved by optimizing the ratio of gelling materials and the design of conductive networks, and an efficient conductive network is formed to ensure high power and long Direct electrocuring of time and high temperature.

Benefits of technology

On-site casting and in-situ high-temperature curing are achieved, the compactness, mechanical properties and radiation shielding capacity of concrete are improved, engineering costs are reduced, maintenance period is shortened, and the stability and efficiency of conductive capacity are ensured.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119263728A_ABST
    Figure CN119263728A_ABST
Patent Text Reader

Abstract

The invention provides direct electric curing anti-radiation ultra-high performance concrete and a preparation method thereof. The preparation method comprises the following steps: mixing the cementing material with optional conductive powder, fully and uniformly stirring, then adding the water and the water reducing agent, finally adding the iron radiation-proof aggregate and the conductive fibers, and fully and uniformly stirring to obtain the radiation-proof ultra-high-performance concrete material with conductivity. And pouring and molding the concrete material, and then electrifying for electric curing to obtain the anti-radiation ultra-high performance concrete material. Considering that the iron radiation-proof aggregate has electrical conductivity, the electrical conductivity of the concrete can be improved while the ray shielding capability of the concrete is improved, so that high-efficiency direct electric curing of the radiation-proof ultra-high-performance concrete becomes possible, and the method can be used for rapid curing of the cast-in-place radiation-proof ultra-high-performance concrete; the curing period of the anti-radiation ultra-high performance concrete is shortened, the construction efficiency is improved, and the engineering cost is greatly reduced, so that the method has practical and promotional values.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building materials, and in particular to a direct electric curing radiation-proof ultra-high performance concrete and a preparation method thereof. Background Art

[0002] Radiation-proof concrete is currently the most widely used and economical nuclear radiation protection material. Compared with metal and organic polymer protection materials, it has the advantages of a wide source of raw materials, easy construction and low manufacturing cost. As the main structural material for nuclear engineering buildings, it is an important safety guarantee for nuclear energy utilization facilities. Radiation-proof ultra-high performance concrete has the characteristics of ultra-high strength and toughness, and can withstand dynamic loads caused by explosion impact or geological disasters. It is a material that meets the safety protection needs of nuclear engineering. Due to the requirements of the material for impact resistance, the method of using prefabricated components + post-casting strips will produce weak interfaces that affect structural performance. At the same time, high-density components are heavy and inconvenient to construct. Therefore, actual projects are mostly cast-in-place construction methods. This method is difficult to use the commonly used steam and autoclave curing technology for concrete, resulting in the lack of rapid curing methods for radiation-proof ultra-high performance concrete.

[0003] Direct electrical curing is a method of curing concrete by using the induction heat generated by concrete under the action of alternating current. Compared with traditional steam curing, this method has the characteristics of low curing equipment requirements (no curing container is required) and high curing efficiency (almost all the energy is used to heat up the concrete). It only needs to arrange the electrodes to cure the concrete on site, which is suitable for the cast-in-place and curing needs of radiation-proof ultra-high performance concrete. However, when the concrete material is cured at high temperature, it will quickly hydrate itself, consume the free water in the capillaries, and the material resistance will increase significantly, thereby reducing the curing power, resulting in limited heating efficiency of the traditional direct electrical curing method. The heat of direct electrical curing is mostly used to maintain the temperature of the concrete. For example, in cold environment construction and road deicing, the heat is not used to generate high-temperature curing, but to maintain the appropriate temperature of the material itself in the cold environment (ambient temperature is below zero, and the concrete temperature is about 20°C). Related technologies propose a method of using carbon-based high-conductivity fillers such as graphite, carbon fiber, and carbon nanotubes to improve the conductivity of concrete materials, which can achieve its high-efficiency direct electrical curing, but such materials may reduce the strength and density of concrete, or be costly. At the same time, the high specific surface area of ​​conductive fillers also brings about the problem of difficulty in dispersion, limiting their dosage.

[0004] Based on the limitations of the current direct electrical curing method for preparing concrete, it is necessary to make improvements. Summary of the invention

[0005] In view of this, the present invention proposes a direct electrical curing radiation-proof ultra-high performance concrete and a preparation method thereof, so as to solve or partially solve the problems existing in the prior art.

[0006] In a first aspect, the present invention provides a direct electrically cured radiation-proof ultra-high performance concrete, including cementitious materials, iron radiation-proof aggregates, water, a water reducing agent, and conductive fibers.

[0007] Preferably, it also includes conductive powder;

[0008] The cementitious materials include cement, silica fume, and fly ash microbeads;

[0009] And / or, the conductive powder includes at least one of copper powder, iron powder and titanium dioxide;

[0010] And / or, the iron radiation-proof aggregate includes at least one of ilmenite sand and steel forging;

[0011] And / or, the conductive fiber includes at least one of steel fiber, copper-plated steel fiber, and carbon fiber.

[0012] Preferably, the particle size of the conductive powder is less than 0.15 mm;

[0013] The particle size of the iron radiation-proof aggregate is 0.15 to 4.75 mm;

[0014] The length of the conductive fiber is 4 to 14 mm.

[0015] Preferably, the mass ratio of the cement, silica fume, fly ash microbeads, iron radiation-proof aggregate, water, and water-reducing agent is (650-780):(120-180):(150-200):(1600-2400):(180-250):(20-30);

[0016] The conductive powder accounts for 10-20% of the mass fraction of the gelling material used;

[0017] The conductive fibers account for 2-2.5 vol% of the volume of the radiation-proof ultra-high performance concrete material.

[0018] Preferably, the mass ratio of the cement, silica fume, fly ash beads, iron radiation protection aggregate, water, water reducer, conductive powder and conductive fiber is: (650-780):(120-180):(150-200):(1600-2400):(180-250):(20-30):(0-140):(120-200).

[0019] In a second aspect, the present invention further provides a method for preparing the direct electrical curing radiation-proof ultra-high performance concrete, comprising the following steps:

[0020] The cementitious material and the conductive powder are mixed and stirred, and then water and a water reducing agent are added, and finally iron radiation-proof aggregate and conductive fibers are added and stirred to obtain a radiation-proof ultra-high performance concrete material with conductivity;

[0021] The concrete material is poured into a forming mold with electrode sheets at both ends, pre-cured and demolded, and then alternating current is applied for constant power electrical curing. After reaching the curing age, a radiation-proof ultra-high performance concrete material is obtained.

[0022] Preferably, the concrete material is poured into a mold to be formed, and electrodes made of copper mesh are inserted at both ends of the concrete, and then placed in a standard curing box for pre-curing for one day;

[0023] Among them, the standard curing temperature is 20±2℃ and the relative humidity is above 95%.

[0024] Preferably, the electrical maintenance power is 10 to 60 W;

[0025] And / or, perform constant power electrical maintenance to reach a maintenance age, wherein the maintenance age is 6 to 24 hours.

[0026] Preferably, the cementitious material and the conductive powder are mixed and stirred for 3 to 5 minutes, water and a water reducing agent are added, and stirring is continued for 2 to 3 minutes, and finally iron radiation-proof aggregate and conductive fibers are added and stirred for 3 to 4 minutes to obtain a conductive radiation-proof ultra-high performance concrete material.

[0027] The direct electrical curing radiation-proof ultra-high performance concrete and the preparation method thereof of the present invention have the following beneficial effects compared with the prior art:

[0028] 1. The present invention uses the direct electrical curing method for the preparation of radiation-proof ultra-high performance concrete, which meets the engineering requirements of on-site pouring and in-situ high-temperature curing, and provides an effective measure for the rapid construction of fortifications using such materials;

[0029] 2. In terms of improving the conductivity of concrete, the role of aggregates has not been taken seriously. Although aggregates are granular, they are not conducive to overlapping each other to form a conductive network. Even if UHPC uses conductive aggregates, it is difficult to reach the percolation threshold (there is a slurry lubrication layer between aggregates, which becomes an insulating layer after hardening). In the present invention, since the volume proportion of aggregates in concrete is high, conductive aggregates and fibers are easy to overlap to form a conductive network, and aggregate conductivity can be compatible with other forms of conductive networks; the present invention utilizes the advantages of high density and excellent conductivity of iron radiation-proof aggregates, steel fibers and metal conductive powders, and improves the radiation shielding ability of ultra-high performance concrete by incorporating the above materials. At the same time, an effective conductive network is built in the ultra-high performance concrete, so that the ultra-high performance concrete will not lose its conductivity due to rapid hydration of the slurry, and high-power, long-term, and high-curing temperature direct electrical curing is achieved;

[0030] 3. The present invention optimizes well-graded cementitious materials, metal conductive powders and radiation-proof aggregates, designs mix ratios based on the MAA model, and achieves the closest packing between particles of various materials. On the one hand, it improves the density, mechanical properties and radiation shielding ability of ultra-high performance concrete, and on the other hand, it promotes the mutual contact between various conductive fillers, ensuring efficient connection of the conductive network. BRIEF DESCRIPTION OF THE DRAWINGS

[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the prior art descriptions. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0032] Figure 1 It is a schematic diagram of the electrical maintenance of the present invention;

[0033] Figure 2 The initial resistivity and final resistivity diagrams of the concrete materials prepared in the embodiments and comparative examples;

[0034] Figure 3 The temperature variation curves during the electrical curing of the concrete materials prepared in Example 1 and Example 2;

[0035] Figure 4 The temperature variation curves during the electrical curing process of the concrete materials prepared in Comparative Examples 2 and 3 are shown;

[0036] Figure 5 The temperature variation curve during the electrical curing process of the concrete material prepared in Example 3-5;

[0037] Figure 6 This is a temperature change curve during the electrical curing process of the concrete material prepared in Example 6-7. DETAILED DESCRIPTION

[0038] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0039] It should be noted that the order of description of the following embodiments is not intended to limit the preferred order of the embodiments. In addition, in the description of the present application, the term "including" means "including but not limited to". Various embodiments of the present invention may be in the form of a range; it should be understood that the description in the form of a range is only for convenience and brevity and should not be understood as a rigid limitation on the scope of the present invention; therefore, it should be considered that the range description has specifically disclosed all possible sub-ranges and single numerical values ​​within the range. For example, it should be considered that the range description from 1 to 6 has specifically disclosed sub-ranges, such as from 1 to 3, from 1 to 4, from 1 to 5, from 2 to 4, from 2 to 6, from 3 to 6, etc., as well as single numbers within the numbered ranges, such as 1, 2, 3, 4, 5 and 6, which apply regardless of the range. In addition, whenever a numerical range is indicated in this article, it is meant to include any cited numbers (fractions or integers) within the indicated range.

[0040] The embodiment of the present application provides a direct electrical curing radiation-proof ultra-high performance concrete, including cementitious materials, iron radiation-proof aggregates, water, a water reducing agent, and conductive fibers.

[0041] In some embodiments, the radiation-proof ultra-high performance concrete further includes conductive powder.

[0042] In some embodiments, the cementitious material includes cement, silica fume, and fly ash microspheres.

[0043] In some embodiments, the conductive powder includes at least one of copper powder, iron powder, and titanium dioxide.

[0044] In some embodiments, the ferrous radiation shielding aggregate includes at least one of ilmenite sand and steel forging.

[0045] In some embodiments, the conductive fibers include at least one of steel fibers, copper-coated steel fibers, and carbon fibers.

[0046] In some embodiments, the particle size of the conductive powder is less than 0.15 mm.

[0047] In some embodiments, the particle size of the iron radiation shielding aggregate is 0.15-4.75 mm.

[0048] In some embodiments, the conductive fibers have a length of 4 to 14 mm.

[0049] In some embodiments, the mass ratio of cement, silica fume, fly ash beads, iron radiation protection aggregate, water, and water reducer is (650-780):(120-180):(150-200):(1600-2400):(180-250):(20-30).

[0050] In some embodiments, the conductive powder accounts for 10-20% by weight of the gelling material.

[0051] In some embodiments, the conductive fibers account for 2-2.5 vol% of the radiation shielding ultra-high performance concrete material.

[0052] In some embodiments, the mass ratios of cement, silica fume, fly ash beads, iron radiation protection aggregate, water, water reducer, conductive powder, and conductive fiber are: (650-780):(120-180):(150-200):(1600-2400):(180-250):(20-30):(0-140):(120-200).

[0053] In some embodiments, the cementitious material includes cement, silica fume, and fly ash microspheres. The cement is P.O52.5 silicate cement with a density of 3100 kg / m 3 ; The SiO2 mass content in silica ash is ≥93%, and the density is 2100kg / m 3 , specific surface area ≥13500m 2 / kg; Fly ash microbeads ignition loss ≤4.5%, spherical particle volume ratio ≥91%, density 2500kg / m 3 .

[0054] In some embodiments, the water reducing agent is a polycarboxylic acid-based water reducing agent, and the water reducing rate is ≥30%.

[0055] In some embodiments, the conductive powder is preferably copper powder and iron powder, the particle size distribution range of the conductive powder is 50 μm-150 μm, and the density of the copper powder is 8.8-9.2 g / cm 3 , the density of iron powder is 6.7~7.8g / cm 3 .

[0056] In some embodiments, the iron radiation shielding aggregate is preferably ilmenite sand with a continuous grade of 0.15-4.75 mm, and the apparent density of the ilmenite sand is 4400-4500 kg / m 3 .

[0057] In some embodiments, the conductive fibers are preferably steel fibers and carbon fibers, with a steel fiber diameter of 0.2-0.3 mm, a nominal length of 13 mm, and a tensile strength of ≥2850 MPa; a carbon fiber monofilament diameter of 7-10 μm, a length of 4 mm, a tensile strength of 3.6-3.8 GPa, a carbon content of ≥95%, and a density of 1.76 g / cm 3 .

[0058] Based on the same inventive concept, the present invention also provides a method for preparing the above-mentioned direct electrical curing radiation-proof ultra-high performance concrete, comprising the following steps:

[0059] S1. Mixing and stirring a cementitious material and an optional conductive powder, adding water and a water reducing agent, and finally adding iron radiation-proof aggregate and conductive fibers and stirring to obtain a radiation-proof ultra-high performance concrete material with conductivity;

[0060] S2. Pour the concrete material into a forming mold with electrode sheets at both ends, perform pre-curing, demoulding, and then apply alternating current for constant power electrical curing. After reaching the curing age, a radiation-proof ultra-high performance concrete material is obtained.

[0061] The present invention takes into account the electrical conductivity of iron radiation-proof aggregates, and can improve the radiation shielding capability of concrete while improving its electrical conductivity, making efficient direct electrical curing of radiation-proof ultra-high performance concrete possible. It can be used for the rapid curing of cast-in-place radiation-proof ultra-high performance concrete, shortening the curing period of radiation-proof ultra-high performance concrete, improving construction efficiency, and significantly reducing engineering costs, and therefore has practical and promotional value.

[0062] In some embodiments, concrete material is poured into a mold to form, and electrodes made of copper mesh are inserted at both ends of the concrete, and then the concrete is placed in a standard curing box for pre-curing for one day;

[0063] Among them, the standard curing temperature is 20±2℃ and the relative humidity is above 95%.

[0064] In some embodiments, the electrical maintenance power is 10-60W.

[0065] In some embodiments, constant power electrical maintenance is performed to reach a maintenance age, wherein the maintenance age is 6 to 24 hours.

[0066] In some embodiments, the cementitious material is mixed with an optional conductive powder and stirred for 3 to 5 minutes, water and a water reducer are added, and stirring is continued for 2 to 3 minutes. Finally, iron radiation-proof aggregate and conductive fiber are added and stirred for 3 to 4 minutes to obtain a conductive radiation-proof ultra-high performance concrete material.

[0067] The present invention uses a direct electrical curing method for the preparation of radiation-proof ultra-high performance concrete, realizes the engineering requirements of on-site pouring and in-situ high-temperature curing, and provides an effective measure for the rapid construction of fortifications using such materials; in terms of improving the conductivity of concrete, the role of aggregates has not been taken seriously. Although aggregates are granular, they are not conducive to overlapping each other to form a conductive network. Even if UHPC uses all conductive aggregates, it is difficult to reach the percolation threshold (there is a slurry lubrication layer between aggregates, which becomes an insulating layer after hardening). In the present invention, since the volume proportion of aggregates in concrete is high, conductive aggregates and fibers are easily overlapped to form a conductive network, and aggregate conductivity is compatible with other forms of conductive networks; the present invention utilizes iron radiation-proof aggregates, steel fibers and The advantages of high density and excellent conductivity of metal conductive powder and the like are achieved by adding the above materials to improve the radiation shielding ability of ultra-high performance concrete. At the same time, an effective conductive network is built in the ultra-high performance concrete, so that the ultra-high performance concrete will not lose its conductivity due to rapid hydration of the slurry, thereby achieving direct electrical curing with high power, long time and high curing temperature. The present invention optimizes well-graded cementitious materials, metal conductive powder and radiation-proof aggregates, designs the mix ratio based on the MAA model, and achieves the closest stacking between particles of various materials. On the one hand, it improves the density, mechanical properties and radiation shielding ability of ultra-high performance concrete, and on the other hand, it promotes the mutual contact between various conductive fillers, thereby ensuring the efficient connection of the conductive network.

[0068] For further reference, Figure 1 As shown, it shows a schematic diagram of electrical curing, which is to convert concrete materials (i.e. Figure 1 A concrete test block is poured into a mold to form a concrete test block, and electrodes made of copper mesh are inserted at both ends of the concrete. Then, alternating current is applied. Specifically, a variable frequency AC power supply is connected to the electrode, alternating current is applied, and changes in resistivity and curing temperature are monitored throughout the process.

[0069] The following further illustrates the direct electric curing radiation-proof ultra-high performance concrete of the present invention with specific examples. This section further illustrates the content of the present invention in conjunction with specific examples, but should not be construed as limiting the present invention. Unless otherwise specified, the technical means used in the examples are conventional means well known to those skilled in the art. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0070] The cement used in the following examples is Tongling Conch P·O52.5 ordinary Portland cement;

[0071] The silica fume used was produced by Sichuan Tianlang Silica Powder Material Co., Ltd., with a SiO2 mass content of 95% and a specific surface area of ​​18500m 2 / kg, 28d activity index 108%;

[0072] The fly ash microspheres used were produced by Tianjin Zhicheng New Material Technology Co., Ltd. and have a specific surface area of ​​1350m 2 / kg, activity coefficient 105%, water requirement ratio 85%, apparent density 2510kg / m 3 ;

[0073] The ilmenite sand used was produced by Lingshou County Bocai Mineral Products Processing Plant, with an apparent density of 4430kg / m 3 , particle size 0.15-2.36mm;

[0074] All the quartz sand is produced by Xiamen Ace Standard Sand Co., Ltd.

[0075] The steel fiber used was produced by Wuhan Road and Bridge Co., Ltd., with a fiber diameter of 0.2-0.3 mm, a nominal length of 13 mm, and a tensile strength of 2950 MPa;

[0076] The carbon fiber used is Japanese Toray chopped fiber, with a single fiber diameter of 7 μm, a length of 4 mm, a tensile strength of 3.9 GPa, a carbon content of 97%, a resistivity of 1.0-1.3 Ω·cm, and a density of 1.76 g / cm 3 ;

[0077] The water reducing agent used is a polycarboxylic acid water reducing agent produced by Jiangsu Subote, with a water reducing rate of ≥30%;

[0078] The copper powder and iron powder used were produced by Nangong Zhongye Xindun Alloy Co., Ltd., with a particle size of 50-150 μm. The density of copper powder was 8.9 g / cm 3 , the density of iron powder is 7.7g / cm 3 .

[0079] Example 1

[0080] This embodiment provides a direct electrical curing radiation-proof ultra-high performance concrete, including the following raw materials:

[0081] Cement 720kg / m 3 、Silica fume 150kg / m 3 , fly ash microbeads 180kg / m 3 、Ilmenite sand 1900kg / m 3 , Steel fiber 200kg / m 3 , water reducing agent 25kg / m 3 , water 200kg / m 3 .

[0082] The method for preparing the above-mentioned radiation-proof ultra-high performance concrete material comprises the following steps:

[0083] S1. Add cement, silica fume and fly ash microbeads into a mixer, stir slowly (stirring speed 145r / min) for 3min until uniform, then add water reducer and water and stir slowly for 3min to make slurry, then add ilmenite sand and steel fiber and stir slowly for 2min, and finally stir quickly (stirring speed 285r / min) for 1min to make radiation-proof ultra-high performance concrete material;

[0084] S2. Pour the concrete material prepared in S1 into a forming mold with electrode sheets placed at both ends, and then put it into a standard curing box for pre-curing for one day; demold, measure the initial resistivity, and then apply alternating current, perform curing at a constant power of 20W and record the resistivity and temperature changes of the concrete material, cool to room temperature after a curing age of 8h, and then test its mechanical properties and radiation shielding properties; wherein, the standard curing temperature is 20°C and the relative humidity is 98%.

[0085] Example 2

[0086] The radiation-proof ultra-high performance concrete provided in the embodiment of the present application is basically the same as that in Embodiment 1, except that the constant electric power of the direct electric curing in step S2 is 30W.

[0087] Comparative Example 1

[0088] The radiation-proof ultra-high performance concrete provided in the comparative example of the present application is basically the same as that in Example 1, except that the standard curing time in step S2 is 28 days, and no electrical curing is performed;

[0089] The specific step S2 is: pouring the concrete material prepared in S1 into a forming mold with electrode sheets placed at both ends, and then placing it in a standard curing box for pre-curing for 28 days; demolding, and testing its mechanical properties and radiation shielding properties; wherein the standard curing temperature is 20°C and the relative humidity is 98%.

[0090] Comparative Example 2

[0091] The ultra-high performance concrete provided in the comparative example of this application includes the following raw materials:

[0092] Cement 720kg / m 3 、Silica fume 150kg / m 3 , fly ash microbeads 180kg / m 3 , Quartz sand 1400kg / m 3 , Steel fiber 200kg / m 3 , water reducing agent 25kg / m 3 , water 200kg / m 3 .

[0093] The method for preparing the above ultra-high performance concrete material comprises the following steps:

[0094] S1. Add cement, silica fume and fly ash microbeads into a mixer, stir slowly (stirring speed 145r / min) for 3min until uniform, then add water reducer and water and stir slowly for 3min to make slurry, then add quartz sand and steel fiber and stir slowly for 2min, and finally stir quickly (stirring speed 285r / min) for 1min to make radiation-proof ultra-high performance concrete material;

[0095] S2. Pour the concrete material prepared in S1 into a forming mold with electrode sheets placed at both ends, and then put it into a standard curing box for pre-curing for one day; demold, measure the initial resistivity, and then apply alternating current, perform curing at a constant power of 20W and record the resistivity and temperature changes of the concrete material, cool to room temperature after a curing age of 8h, and then test its mechanical properties and radiation shielding properties; wherein, the standard curing temperature is 20°C and the relative humidity is 98%.

[0096] Comparative Example 3

[0097] The ultra-high performance concrete provided in the comparative example of the present application is the same as that in comparative example 2, except that the constant electric power of the electric curing in step S2 is 30W.

[0098] Comparative Example 4

[0099] The ultra-high performance concrete provided in the comparative example of the present application is the same as that in comparative example 2, except that: the standard curing time in step S2 is 28 days, and no electrical curing is performed;

[0100] The specific step S2 is: pouring the concrete material prepared in S1 into a forming mold with electrode sheets placed at both ends, and then placing it in a standard curing box for pre-curing for 28 days; demolding, and testing its mechanical properties and radiation shielding properties; wherein the standard curing temperature is 20°C and the relative humidity is 98%.

[0101] Example 3

[0102] The radiation-proof ultra-high performance concrete provided in the embodiment of the present application includes the following raw materials:

[0103] Cement 720kg / m 3 、Silica fume 150kg / m 3 , fly ash microbeads 180kg / m 3 、Ilmenite sand 1900kg / m 3 , Steel fiber 100kg / m 3 , Carbon fiber 20kg / m 3 , water reducing agent 25kg / m 3 , water 200kg / m 3 .

[0104] The method for preparing the above-mentioned radiation-proof ultra-high performance concrete material comprises the following steps:

[0105] S1. Add cement, silica fume and fly ash microbeads into a mixer, stir slowly (stirring speed 145r / min) for 3min until uniform, then add water reducer and water and stir slowly for 3min to make slurry, then add ilmenite sand, carbon fiber and steel fiber and stir slowly for 2min, and finally stir quickly (stirring speed 285r / min) for 1min to make radiation-proof ultra-high performance concrete material;

[0106] S2. Pour the concrete material prepared in S1 into a forming mold with electrode sheets placed at both ends, and then put it into a standard curing box for pre-curing for one day; demold, measure the initial resistivity, and then apply alternating current, perform curing at a constant power of 20W and record the resistivity and temperature changes of the concrete material, cool to room temperature after a curing age of 8h, and then test its mechanical properties and radiation shielding properties; wherein, the standard curing temperature is 20°C and the relative humidity is 98%.

[0107] Example 4

[0108] The radiation-proof ultra-high performance concrete provided in the embodiment of the present application is the same as that in Embodiment 3, except that the constant electric power of the electric curing in step S2 is 40W.

[0109] Example 5

[0110] The radiation-proof ultra-high performance concrete provided in the embodiment of the present application is the same as that in Embodiment 3, except that the constant electric power of the electric curing in step S2 is 60W.

[0111] Comparative Example 5

[0112] The radiation-proof ultra-high performance concrete provided in the embodiment of the present application is the same as that in embodiment 3, except that: the standard curing time in step S2 is 28 days, and no electrical curing is performed;

[0113] The specific step S2 is: pouring the concrete material prepared in S1 into a forming mold with electrode sheets placed at both ends, and then placing it in a standard curing box for pre-curing for 28 days; demolding, and testing its mechanical properties and radiation shielding properties; wherein the standard curing temperature is 20°C and the relative humidity is 98%.

[0114] Example 6

[0115] The radiation-proof ultra-high performance concrete provided in the embodiment of the present application includes the following raw materials:

[0116] Cement 720kg / m 3 、Silica fume 150kg / m 3 , fly ash microbeads 180kg / m 3 、Ilmenite sand 1900kg / m 3 , Steel fiber 200kg / m 3 , copper powder 140kg / m3 , water reducing agent 25kg / m 3 , water 200kg / m 3 ;

[0117] The copper powder is an external powder and does not affect the original water-cement ratio.

[0118] The method for preparing the above-mentioned radiation-proof ultra-high performance concrete material comprises the following steps:

[0119] S1. Add cement, silica fume, fly ash microbeads and copper powder into a mixer, stir slowly (stirring speed 145r / min) for 3min until uniform, then add water reducer and water and stir slowly for 3min to make slurry, then add ilmenite sand and steel fiber and stir slowly for 2min, and finally stir quickly (stirring speed 285r / min) for 1min to make radiation-proof ultra-high performance concrete material;

[0120] S2. Pour the concrete material prepared in S1 into a forming mold with electrode sheets placed at both ends, and then put it into a standard curing box for pre-curing for one day; demold, measure the initial resistivity, and then apply alternating current, perform curing at a constant power of 20W and record the resistivity and temperature changes of the concrete material, cool to room temperature after a curing age of 8h, and then test its mechanical properties and radiation shielding properties; wherein, the standard curing temperature is 20°C and the relative humidity is 98%.

[0121] Example 7

[0122] The radiation-proof ultra-high performance concrete provided in the embodiment of the present application includes the following raw materials:

[0123] Cement 720kg / m 3 、Silica fume 150kg / m 3 , fly ash microbeads 180kg / m 3 、Ilmenite sand 1900kg / m 3 , Steel fiber 200kg / m 3 , iron powder 120kg / m 3 , water reducing agent 25kg / m 3 , water 200kg / m 3 ;

[0124] The iron powder is an external powder and does not affect the original water-cement ratio.

[0125] The method for preparing the above-mentioned radiation-proof ultra-high performance concrete material comprises the following steps:

[0126] S1. Add cement, silica fume, fly ash microbeads and iron powder into a mixer, stir slowly (stirring speed 145r / min) for 3min until uniform, then add water reducer and water and stir slowly for 3min to make slurry, then add ilmenite sand and steel fiber and stir slowly for 2min, and finally stir quickly (stirring speed 285r / min) for 1min to make radiation-proof ultra-high performance concrete material;

[0127] S2, pour the concrete material prepared in S1 into a forming mold with electrode sheets at both ends, and then put it into a standard curing box for pre-curing for one day; demoulding, measuring the initial resistivity, and then applying alternating current, curing with a constant power of 20W and recording the resistivity and temperature changes of the concrete material, cooling to room temperature after curing for 8 hours, and then testing its mechanical properties and radiation shielding properties; wherein, the standard curing temperature is 20°C and the relative humidity is 98%. The raw materials and curing systems used in the embodiments and comparative examples listed in the present invention are shown in Table 1.

[0128] Table 1 - Raw materials and curing system used in the examples and comparative examples

[0129]

[0130]

[0131] The changes in the resistivity and temperature of the concrete materials during the curing process of the above-mentioned embodiments and comparative examples were recorded, as shown in Table 2.

[0132] Table 2 - Changes in resistivity and temperature of concrete materials during curing of examples and comparative examples

[0133]

[0134] The basic properties of the concrete materials in the above embodiments and comparative examples were tested, and the results are shown in Table 3.

[0135] Table 3 - Changes in resistivity and temperature of concrete materials during curing of examples and comparative examples

[0136]

[0137]

[0138] In Table 3, HVL refers to the thickness of the radiation shielding layer required to reduce the radiation intensity to half of its initial value. The HVL value is Lambert's law I = I0·e -μt cm -1 The strength of comparative examples 1 and 4 in the table is the compressive strength after standard curing for 28 days, and the strength of other samples is the strength after direct electrical curing, and the age is 32 hours (24 hours + 8 hours = 32 hours).

[0139] Figure 2 Graphs showing the initial resistivity and final resistivity of the concrete materials prepared in the embodiments and comparative examples.

[0140] from Figure 2 As can be seen from Table 2, the radiation-proof ultra-high performance concrete prepared by the present invention has a lower initial resistivity than traditional ultra-high performance concrete, especially its resistivity increases less with the progress of curing (increase in hydration degree), and the resistivity stability is good, so it is suitable for long-term direct electrical curing. In addition, the addition of carbon fiber and conductive powder can also effectively reduce the initial resistivity.

[0141] Figure 3 It is a temperature change curve diagram of the concrete material prepared in Example 1 and Example 2 during the electrical curing process.

[0142] Figure 4 It is a temperature change curve diagram of the concrete materials prepared in Comparative Examples 2 and 3 during the electrical curing process.

[0143] from Figures 3-4 It can be seen that in the early stage of curing, the fresh concrete material can form a good circuit due to sufficient water in the volume, and the conductivity is good and the temperature rises quickly. However, as the curing progresses (the degree of hydration increases), the water content decreases, and the UHPC aggregate is quartz sand, which is not conductive, and the conductivity decreases rapidly, and the curing temperature also decreases. With the increase of curing power, the maximum curing temperature and the average curing temperature will increase.

[0144] The results in Table 3 show that after 8 hours of 20W direct electrical curing in Example 1, the compressive strength of the radiation-proof ultra-high performance concrete reached 84.4% of the compressive strength of the standard curing 28 days in Example 1; after 8 hours of 30W direct electrical curing in Example 2, its compressive strength was equivalent to the standard curing 28 days. The density of the radiation-proof ultra-high performance concrete prepared by the present invention is 3000kg / m 3 Compared with ordinary ultra-high performance concrete, the density is increased by 26.1% to 34.3%, and the gamma-ray attenuation coefficient is increased by 32.2% to 44.7%, and it has excellent radiation shielding capabilities.

[0145] Figure 5 It is a temperature change curve diagram of the concrete material prepared in Example 3-5 during the electrical curing process.

[0146] Figure 6 It is a temperature change curve diagram of the concrete material prepared in Example 6-7 during the electrical curing process.

[0147] from Figures 5-6It can be seen that the addition of carbon fiber can reduce the resistivity of concrete materials, so that high electric power curing and high electric curing temperature can be achieved. Combined with the data of Examples 3 to 5 in Table 3, as the curing power increases, after 8 hours of 20W direct electric curing, the compressive strength of radiation-proof ultra-high performance concrete reaches 94.1% of the compressive strength of 28d standard curing in Example 1; after 8 hours of 40W direct electric curing in Example 4, its compressive strength has exceeded the compressive strength of 28d standard curing; after 8 hours of 60W direct electric curing, its compressive strength is 22.8% higher than the compressive strength of 28d standard curing. The replacement of certain cementitious materials with conductive powder can not only improve the grading of concrete materials, but also reduce the resistivity of concrete materials and increase the electric curing temperature under the same electric power curing.

[0148] It can be understood that the technical features of the above-described embodiments can be arbitrarily combined. In order to make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0149] The above are only preferred embodiments of the present application, and only specifically describe the technical principles of the present application. These descriptions are only for explaining the principles of the present application and cannot be interpreted as limiting the scope of protection of the present application in any way. Based on the explanation here, any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application, and other specific implementation methods of the present application that can be associated with the technicians in this field without creative work, should be included in the scope of protection of the present application.

Claims

1. A direct electrical curing radiation-proof ultra-high performance concrete, characterized in that: It includes cementitious materials, iron radiation-proof aggregates, water, water-reducing agents and conductive fibers.

2. The direct electrical curing radiation-proof ultra-high performance concrete according to claim 1, characterized in that: Also includes conductive powder; The cementitious materials include cement, silica fume, and fly ash microbeads; And / or, the conductive powder includes at least one of copper powder, iron powder and titanium dioxide; And / or, the iron radiation-proof aggregate includes at least one of ilmenite sand and steel forging; And / or, the conductive fiber includes at least one of steel fiber, copper-plated steel fiber, and carbon fiber.

3. The direct electrical curing radiation-proof ultra-high performance concrete according to claim 2, characterized in that: The particle size of the conductive powder is less than 0.15 mm; The particle size of the iron radiation-proof aggregate is 0.15 to 4.75 mm; The length of the conductive fiber is 4 to 14 mm.

4. The direct electrical curing radiation-proof ultra-high performance concrete according to claim 2, characterized in that: The mass ratio of the cement, silica fume, fly ash microbeads, iron radiation-proof aggregate, water and water reducing agent is (650-780):(120-180):(150-200):(1600-2400):(180-250):(20-30); The conductive powder accounts for 10-20% of the mass fraction of the gelling material used; The conductive fibers account for 2-2.5 vol% of the volume of the radiation-proof ultra-high performance concrete material.

5. The direct electrical curing radiation-proof ultra-high performance concrete according to claim 4, characterized in that: The mass ratio of the cement, silica fume, fly ash microbeads, iron radiation-proof aggregate, water, water reducing agent, conductive powder and conductive fiber is: (650~780):(120~180):(150~200):(1600~2400):(180~250):(20~30):(0~140):(120~200)。 6. A method for preparing direct electrical curing radiation-proof ultra-high performance concrete according to any one of claims 1 to 5, characterized in that: The following steps are involved: The cementitious material and the optional conductive powder are mixed and stirred, and then water and a water reducing agent are added, and finally iron radiation-proof aggregate and conductive fibers are added and stirred to obtain a radiation-proof ultra-high performance concrete material with conductivity; The concrete material is poured into a forming mold with electrode sheets at both ends, pre-cured and demolded, and then alternating current is applied for constant power electrical curing. After reaching the curing age, a radiation-proof ultra-high performance concrete material is obtained.

7. The method for preparing the direct electrical curing radiation-proof ultra-high performance concrete according to claim 6, characterized in that: The concrete material is poured into the mold to form, and electrodes made of copper mesh are inserted at both ends of the concrete, and then placed in a standard curing box for pre-curing for one day; Among them, the standard curing temperature is 20±2℃ and the relative humidity is above 95%.

8. The method for preparing the direct electrical curing radiation-proof ultra-high performance concrete according to claim 6, characterized in that: The electrical maintenance power is 10~60W; And / or, perform constant power electrical maintenance to reach the maintenance age, wherein the maintenance age is 6 to 24 hours.

9. The method for preparing the direct electrical curing radiation-proof ultra-high performance concrete according to claim 6, characterized in that: The cementitious material and the optional conductive powder are mixed and stirred for 3 to 5 minutes, and then water and a water reducing agent are added, and stirring is continued for 2 to 3 minutes. Finally, iron radiation-proof aggregate and conductive fiber are added and stirred for 3 to 4 minutes to obtain a conductive radiation-proof ultra-high performance concrete material.